Classification Criteria For Early Knee Osteoarthritis: A Review Article - Herrero-Manley, Luz; Alabajos-Cea, Ana; Suso-Martí, Luis; Viosca-Herrero, Enrique (Aktuelle Rheumatologie, 2023)
Objective The aim of this systematic review (SR) was to define the “state of the art” on classification criteria for early knee osteoarthritis (EKOA).Methods A systematic review was performed using MEDLINE (Pubmed), Web of Science, Scopus, EMBASE, PEDro, CINAHL and Google scholar databases. Two independent reviewers conducted the eligibility review. Any type of study that proposed diagnostic criteria of EKOA was included.Results Seven articles were included according to the inclusion criteria. The evidence presented in this SR shows that there is still no consensus regarding definition and classification of EKOA. At present, there are seven different proposals in the scientific literature, and they only agree on including knee pain and radiographic evaluation in their criteria, but they do not even consider the same situations for including these two factors.Conclusion There is still no consensus regarding definition and classification of EKOA. Knee pain and radiological assessment seem to be the most commonly used criteria, but due to the variability encountered, it is not possible to reach a consensus on a clear definition and diagnosis of EOKA.
Keywords: diagnosis criteria; early osteoarthritis; knee osteoarthritis